One of the least disturbed marine coastal ecosystems on Earth: Spatial and temporal persistence of Darwin's sub-Antarctic giant kelp forests - Mora-Soto, Alejandra; Capsey, Austin; Friedlander, Alan M.; Palacios, Mauricio; Brewin, Paul E.; Golding, Neil; Dayton, Paul; Van Tussenbroek, Brigitta; Montiel San Martin, Americo Manuel; Goodell, Whitney; Velasco-Charpentier, Catalina; Hart, Tom; et al. (My University, 2021)
Aim Marine habitats and their dynamics are difficult to systematically monitor, particularly those in remote locations. This is the case with the sub-Antarctic ecosystem of the giant kelp Macrocystis pyrifera, which was already noted by Charles Darwin in his accounts on the Voyage of the Beagle and recorded on the nautical charts made during that expedition. We combined these and other nautical charts from the 19th and early 20th centuries with surveys conducted in the 1970s and 1980s and satellite detection algorithms from 1984 to 2019, to analyse kelp distribution through time and the factors that correlate with it. Location Marine ecoregions of Channels and Fjords of Southern Chile, Falkland Islands (Malvinas), and the island of South Georgia. Taxon Macrocystis pyrifera. Methods We characterised 309 giant kelp forests by their coastal geospatial attributes. Statistically significant variables were included in a conditional inference tree to predict kelp forest size. Sea surface temperature (SST) records were analysed to confirm temperature ranges over the last four decades. Nautical charts, historical surveys, aerial photogrammetry, unmanned aerial vehicle (UAV) surveys and satellite imagery were overlaid to assess spatial distribution of kelp forest canopies, spanning the period 1829-2020. Results Considering the extensive natural and human caused changes over the last two centuries, this diverse kelp ecosystem is remarkably persistent. We found that the ocean currents and wave exposure, combined with the geomorphological settings of the coastline are the most critical factors predicting the extent of the kelp forests. Main conclusions We have described the long-term ecological persistence of the kelp forests in this vastly under-studied region that offers a conceptual biogeographical model supporting the global importance proposed by Charles Darwin 200 years ago (Darwin, 1845). In the current context of global change, the need for conservation of this persistent and well-preserved marine ecosystem has never been more important.
Keywords: abiotic habitat; coastal biogeography; giant kelp forests; historical cartography; macrocystis pyrifera; nautical charts; remote sensing; sub-antarctic marine ecosystems; the voyage of the beagle